2020
DOI: 10.1186/s12967-020-02453-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiling identifies epigenetic signatures of gastric cardiac intestinal metaplasia

Abstract: Background: Measuring the DNA methylome may offer the opportunity to identify novel disease biomarkers and insights into disease mechanisms. Although aberrant DNA methylation has been investigated in many human cancers and precancerous lesions, the DNA methylation landscape of gastric cardiac intestinal metaplasia (IM) remains unknown. Therefore, we aimed to investigate the genome-wide DNA methylation landscape and to search for potential epigenetic biomarkers of gastric cardiac IM. Methods: Histopathologic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Another study performed the analysis of DNA methylation in gastric cardiac mucosa. It revealed that apart from promoter hypermethylation, a reduced mRNA expression of the homeobox A5 (HOXA5) gene (which functions as a tumor suppressor in the development of GC) was also observed in gastric cardiac IM, suggesting a possible role of this gene in the development of gastric IM [62]. A Brazilian study investigated the expression of telomerase reverse transcriptase (TERT) gene mRNA in normal gastric mucosa, precancerous gastric lesions, and gastric cancer.…”
Section: Genetic Variations In Immentioning
confidence: 99%
“…Another study performed the analysis of DNA methylation in gastric cardiac mucosa. It revealed that apart from promoter hypermethylation, a reduced mRNA expression of the homeobox A5 (HOXA5) gene (which functions as a tumor suppressor in the development of GC) was also observed in gastric cardiac IM, suggesting a possible role of this gene in the development of gastric IM [62]. A Brazilian study investigated the expression of telomerase reverse transcriptase (TERT) gene mRNA in normal gastric mucosa, precancerous gastric lesions, and gastric cancer.…”
Section: Genetic Variations In Immentioning
confidence: 99%
“…All cells were cultured in endothelial cell culture medium for 10-15 generations to eliminate the effects of cell growth factors produced by naive protocells as much as possible. All media were composed of 500 mL basal nutrients, 25 mL fetal bovine serum, 5 mL endothelial cell growth factors, and 5 mL penicillin solution ( 41 ). When the cells were more than 90% confluent, the medium was replaced, and the cells were washed several times with 2 mL phosphate buffered saline (PBS) to eliminate the residual cell growth factors.…”
Section: Methodsmentioning
confidence: 99%
“…Reagents A and B were mixed and incubated for 20 min. The mixed reagent (400 μ L per well) was added to the corresponding 24-well plate, which was replaced with serum containing colorectal cell culture medium after 6 h ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…Differences in commitment between complete and incomplete IM are also highlighted by the different expression of gastric (SOX2) and intestinal (CDX2) transcription factors: while CDX2 is expressed in all types of IM, SOX2 is negative in 93% of complete IM and positive in 85% of incomplete types [ 60 ]. Despite the fact that some authors [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] suggest that incomplete IM is associated with increased risk of GC, there is no conclusive evidence of differences in cancer progression among IM types, and IM characterization is not currently recommended in clinical practice [ 59 ].…”
Section: Precursor Lesions Of Intestinal Type Adenocarcinoma and Their Molecular Alterationsmentioning
confidence: 99%
“…In contrast, global intragenic hypomethylation has not been detected in IM, representing a later event in Correa’s cascade. Finally, Lin and colleagues [ 69 ] suggest that hypermethylation of HOXA5 has a role in the development of gastric cardiac IM.…”
Section: Precursor Lesions Of Intestinal Type Adenocarcinoma and Their Molecular Alterationsmentioning
confidence: 99%